Chemically and thermally stable, emissive carbon dots as viable alternatives to semiconductor quantum dots for emissive nematic liquid crystal–nanoparticle mixtures with lower threshold voltage. Issue 2 (26th January 2016) - Urbanski, Martin; Mirzaei, Javad; Sharma, Anshul; Hofmann, Daniel; Kitzerow, Heinz-S.; Hegmann, Torsten
ABSTRACT: Dispersions of chemically and thermally robust carbon dots (2.5 ± 0.5 nm in core diameter) were prepared and investigated by polarised optical microscopy, electro-optic measurements including dynamic tests and numerical simulations as well as fluorescence confocal microscopy. The carbon dots were prepared by a straightforward thermal decomposition method from citric acid and hexadecylamine, and they show typical excitation wavelength-dependent photoluminescence behaviour. All dispersions, ranging from 0.5 to 5.0 wt.%, showed lower values for isotropic–nematic phase transition temperature and broader isotropic–nematic biphasic temperature intervals with increasing carbon dot content in comparison to the neat material. Doping of the nematic host with the carbon dots resulted in lower values for the apparent threshold voltage and the elastic constants, but higher values for the rotational viscosity. At 2.5 wt.% and higher, carbon dots residing at the confining interfaces in planar cells induce an increasing initial pre-tilt of up to 8° at lower temperatures. Fluorescence confocal microscopy confirmed this, where the luminescence of the carbon dots permitted visualisation of the distribution of the carbon dots in the bulk with a noticeable, in some cases even pattern-like, segregation to the confining interfaces. GRAPHICAL ABSTRACT: